2021
DOI: 10.1016/j.nicl.2021.102899
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic pathways and resting-state functional connectivity in Parkinson’s disease with freezing of gait

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 88 publications
2
9
0
Order By: Relevance
“…Pasquini et al 35 described gait disturbances predicted by early caudatal dysfunction, which goes beyond the scope of this study which did not specifically address gait. However, our results also support an involvement in gait difficulties since significant changes in FOG-Q were observed between both visits and were moderately associated with dopamine depletion in the right caudate and its connectivity to the SPCl 45 .…”
Section: Discussionsupporting
confidence: 76%
“…Pasquini et al 35 described gait disturbances predicted by early caudatal dysfunction, which goes beyond the scope of this study which did not specifically address gait. However, our results also support an involvement in gait difficulties since significant changes in FOG-Q were observed between both visits and were moderately associated with dopamine depletion in the right caudate and its connectivity to the SPCl 45 .…”
Section: Discussionsupporting
confidence: 76%
“…Dysfunctional network connectivity between subcortical and cortical areas extended beyond cognitive and sensorimotor areas, also affecting visuospatial networks. In PD patients with FoG, abnormal FC was observed between the visual cortex, mainly of the right hemisphere, and left caudate ( Steidel et al, 2021 ), right PPN ( Wang et al, 2016 ), bilateral thalamus and GPe ( Potvin-Desrochers et al, 2019 ), when compared to PD patients without FoG. Moreover, two studies found distinct FC alterations between cerebellar and parieto-occipital regions.…”
Section: Structural and Resting-state Functional Connectivity Studies...mentioning
confidence: 96%
“… Functional connectivity (FC) Whole brain and ROI seed-based analyses Cross-sectional Correlational (indirect with behavioral measures of gait) Higher FC between left GP and primary somatosensory cortex (C/T FoG-) correlate positively with behavioral measures of FoG. Lower FC between the left vestibular cortex and regions of the DMN (C/T FoG-) Interference AND/OR Perceptual Dysfunction Pietracupa et al (2018) 21 FoG+ 16 FoG- 19 HC OFF H&Y, LEDD, MMSE, UPDRS-III, FAB, HAM-D, FoG-Q and TUG Structural DTI Cross-sectional Correlational (indirect with FoG-Q and neuropsycho-logical test scores) Widespread WM disruption [predominantly in the right hemisphere between motor, cognitive & limbic structures (C/T HC)] correlates positively with cognitive scores (FAB) Interference Potvin-Desrochers et al (2019) 14 FoG+ 13 FoG- ON H&Y, UPDRS-III, HADS, MoCA, and new FOG-Q Functional connectivity (FC) Subcortical structures seed- to-voxel analysis Cross-sectional Higher FC of bilateral thalamus and bilateral GPe with visual areas (C/T FoG-) Perceptual Dysfunction Steidel et al (2021) 27 FoG+ 32 FoG- OFF H&Y, LEDD, MMSE, PANDA, PDQ39, UPDRS-III, BDI-II, tests for attention, memory, language, executive & visuospatial functions, and FoG-Q Functional connectivity (FC), seed-based analysis (left caudate cluster or ventral tegmental area, VTA) Cross-sectional Correlational (indirect with FoG-Q scores and dopaminergic degeneration) Higher FC between bilateral VTA & DMN regions and higher FC between left caudate & right visual cortex (C/T FoG-) correlate negatively with dopamine levels. In all PD: positive correlation of FoG-Q and FC of VTA with DMN regions.…”
Section: Structural and Resting-state Functional Connectivity Studies...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with PD FOG-patients, PD FOG+ patients showed decreased BC in the right CAU. A resting-state functional MRI (rs-fMRI) study suggested that altered functional connectivity in the CAU may cause damage to the executive function of PD FOG+ patients (Steidel et al, 2021). Thus, the decreased BC in the right CAU may be an important aspect leading to FOG, which is also an important distinction between PD FOG+ and PD FOG-.…”
Section: The Difference In Nodal Parameters Between Groupsmentioning
confidence: 99%